Respuesta :
Hello!
You solve this algebraically
4(m + 9) = -2(m - 5) + 2
Distribute the 4
4m + 36 = -2(m - 5) + 2
Distribute the -2
4m + 36 = -2m + 10 + 2
combine like terms
4m + 36 = -2m + 12
Add 2m to both sides
6m + 36 = 12
Subtract 36 from both sides
6m = -24
Divide both sides by 6
m = -4
Hope this helps!
You solve this algebraically
4(m + 9) = -2(m - 5) + 2
Distribute the 4
4m + 36 = -2(m - 5) + 2
Distribute the -2
4m + 36 = -2m + 10 + 2
combine like terms
4m + 36 = -2m + 12
Add 2m to both sides
6m + 36 = 12
Subtract 36 from both sides
6m = -24
Divide both sides by 6
m = -4
Hope this helps!
m is equal to 4
[tex]4(m + 9 ) = - 2(m - 5) + 2 \\ 4m + 36 = - 2m + 10 + 2 \\ 4m + 2m = 10 + 2 - 36 \\ 6m = - 24 [/tex]
[tex] m = - \frac{24}{6} = - 4[/tex]
good luck
[tex]4(m + 9 ) = - 2(m - 5) + 2 \\ 4m + 36 = - 2m + 10 + 2 \\ 4m + 2m = 10 + 2 - 36 \\ 6m = - 24 [/tex]
[tex] m = - \frac{24}{6} = - 4[/tex]
good luck